BAFF neutralization impairs the autoantibody-mediated clearance of dead adipocytes and aggravates obesity-induced insulin resistance - Lempicki, Melissa D.; Gray, Jake A.; Abuna, Gabriel; Murata, Ramiro M.; Divanovic, Senad; McNamara, Coleen A.; Meher, Akshaya K. (Frontiers in Immunology, 2024)
B cell-activating factor (BAFF) is a critical TNF-family cytokine that regulates homeostasis and peripheral tolerance of B2 cells. BAFF overproduction promotes autoantibody generation and autoimmune diseases. During obesity, BAFF is predominantly produced by white adipose tissue (WAT), and IgG autoantibodies against adipocytes are identified in the WAT of obese humans. However, it remains to be determined if the autoantibodies formed during obesity affect WAT remodeling and systemic insulin resistance. Here, we show that IgG autoantibodies are generated in high-fat diet (HFD)-induced obese mice that bind to apoptotic adipocytes and promote their phagocytosis by macrophages. Next, using murine models of obesity in which the gonadal WAT undergoes remodeling, we found that BAFF neutralization depleted IgG autoantibodies, increased the number of dead adipocytes, and exacerbated WAT inflammation and insulin resistance. RNA sequencing of the stromal vascular fraction from the WAT revealed decreased expression of immunoglobulin light-chain and heavy-chain variable genes suggesting a decreased repertoire of B cells after BAFF neutralization. Further, the B cell activation and the phagocytosis pathways were impaired in the WAT of BAFF-neutralized mice. In vitro, plasma IgG fractions from BAFF-neutralized mice reduced the phagocytic clearance of apoptotic adipocytes. Altogether, our study suggests that IgG autoantibodies developed during obesity, at least in part, dampens exacerbated WAT inflammation and systemic insulin resistance.